Case report: New perspectives on gait initiation strategies from a case of full toes amputation in a professional mountain climber - Storniolo, Jorge L.; Farinelli, Veronica; Onesti, Mattia; Correale, Luca; Peyré-Tartaruga, Leonardo A.; Esposti, Roberto; Cavallari, Paolo (Frontiers in Human Neuroscience, 2024)
We studied a 52-year-old professional mountain climber who underwent bilateral amputation of all five toes after severe frostbite. Two tasks were examined: static posturography (SP) and gait initiation (GI), both performed barefoot and with prosthetic shoes. During SP, the participant kept the upright stance for 30 s while an optoelectronic system with reflective markers recorded feet position and body sway, and two force plates measured the Center of Pressure (CoP) displacement and Ground Reaction Force (GRF) of each foot. During GI, the participant stood on the force plates for at least 10 s and then spontaneously started walking, while optoelectronic system was used to monitor heel-off events; wireless EMG probes recorded the anticipatory postural adjustments (APAs) in trunk and lower limb muscles. Compared to shod condition, during barefoot SP the participant showed a reduced anteroposterior (AP) and mediolateral (ML) extension of the Base of Support (BoS), and the whole-body CoP shifted about 7 mm more anteriorly, approaching the "safer" geometric center of the BoS. Despite this difference, the AP and ML ranges of CoP oscillations were similar in both conditions. In GI, the trunk dorsal muscles showed different APA patterns: when barefoot they were excitatory in the trailing and inhibitory in the leading side while they were bilaterally inhibitory when shod. Thus, in parallel to CoP shift toward a "safer" position in SP, in barefoot GI the body rotation toward the trailing side may reveal a more "cautious" approach; this also shows that different postural strategies may be adopted in GI by one and the same individual.